Co-coon / Aina Insyirah Ismail - Ismail, Aina Insyirah (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
Understanding one’s heritage through arts and culture remains an important part of carving out an utopian future. Sadly, when communities and households adapt to the social and economic changes brought on by globalisation, new technology, and development initiatives, cultural changes unavoidable. Proposing youth haven that use organic, shared spaces inspired by pottery rekindles artistic and cultural expression. Ethnic communities can be empowered socially, culturally and economically through pottery, a pratice that was previously prevalent in Sarawak. Inspired by Sodeisga, avant-garde pottery movement in Japan, the youth haven aims to encourage emotional expression for the youth within a safe sharing space - a cocoon.